SZOnline: Ein integriertes Informationssystem für Online-Sprachunterricht und automatis- ierte Sprachtests - Kamm, Roland; Tiutenko, Arthur (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
The language didactics places the main focus on active, systematic knowledge transfer from a teacher to a learner and on frequent exercise rather then on self-studying and gradual knowledge acquisition as in the didactics of most other (usually academic) subjects. For the quality of computer-based language teaching not only constant interaction of a learner with the teacher or the study colleagues is essential but also with the technical system that organizes, directs and as possi- ble controls the learning process. We consider a technical system for online teaching of languages as a part of a broad IT infrastructure in a language institute. A concept of such software is presented in the following article.
Keywords: E-Learning